2017
DOI: 10.1016/j.ebiom.2017.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Genetic- and Lifestyle-dependent Dental Caries Defined by the Acidic Proline-rich Protein Genes PRH1 and PRH2

Abstract: Dental caries is a chronic infectious disease that affects billions of people with large individual differences in activity. We investigated whether PRH1 and PRH2 polymorphisms in saliva acidic proline-rich protein (PRP) receptors for indigenous bacteria match and predict individual differences in the development of caries. PRH1 and PRH2 variation and adhesion of indigenous and cariogenic (Streptococcus mutans) model bacteria were measured in 452 12-year-old Swedish children along with traditional risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 43 publications
0
46
0
Order By: Relevance
“…The failure of oral hygiene in prediction among this population could due to their genetic background. Strömberg et al indicated that individuals with a specific genetic background may develop more caries from bad oral hygiene than individuals with other genetic backgrounds (54). Hence, variables such as PlI and tooth brushing frequency could still be predictable in other populations with different genetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…The failure of oral hygiene in prediction among this population could due to their genetic background. Strömberg et al indicated that individuals with a specific genetic background may develop more caries from bad oral hygiene than individuals with other genetic backgrounds (54). Hence, variables such as PlI and tooth brushing frequency could still be predictable in other populations with different genetic backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“… 17 These high-caries cases derive from an immune deficiency or carriage of high virulence strains of Streptococcus mutans , consistent with their non-responder behaviour. 18 19 By contrast, the low-to-moderate risk children develop caries as expected from eating and oral hygiene habits. 18 Therefore, the NICE study aims to evaluate the oral health of all participating children in order to better understand the link between impaired immune maturation and the risk for caries development.…”
Section: Introductionmentioning
confidence: 99%
“… 18 19 By contrast, the low-to-moderate risk children develop caries as expected from eating and oral hygiene habits. 18 Therefore, the NICE study aims to evaluate the oral health of all participating children in order to better understand the link between impaired immune maturation and the risk for caries development.…”
Section: Introductionmentioning
confidence: 99%
“…In EBioMedicine , Strömberg et al combined specific human genotypes with susceptibility of dental caries, revealing the evidence of variation in specific human genes ( Strömberg et al, 2017 ). PRH1 and PRH2 variation and adhesion of indigenous and cariogenic ( S. mutans ) model bacteria were measured in 452 12-year-old Swedish children along with traditional risk factors and related to caries at baseline and after 5-years.…”
mentioning
confidence: 99%
“…As present etiological studies of dental caries focus on correlations between microbial load and life style habits, few studies have been done on the correlations between specific host genotypes, microbial load and caries, which is the highlight of this study by Strömberg et al (2017) . Host genotypes, microbiomes, life style, oral hygiene, and disease process may as independent influential factors have great potential to correlate with each other, contributing to the complex etiological network of dental caries.…”
mentioning
confidence: 99%